The Effect of Information Technology Culture on Online Business Success in Jakarta - Gilbert Orville; Rodhiah Rodhiah (Budapest International Research and Critics University, 2022)
Based on the increasingly large development of the internet, the use of the Internet has entered in various fields of life. Everyone can access the Internet; entrepreneurs also take advantage of this as an opportunity. The influence of information technology affects entrepreneurs to make the transition of their business into an online business. That way, the products they sell can be purchased via the internet. This study aims to determine the influence of information technology culture on online business success, the effect of one's innovation and experience on the relationship between information technology culture and online business success in Jakarta. The population in this study are online entrepreneurs in Jakarta. The sample used in this study amounted to 100 samples. This sample selection technique uses convenience sampling technique through SmartPLS 3. Data collection is done by distributing questionnaires through Google Form. The results of this study indicate that the information technology culture variable has a positive and significant effect on online business success, the experience variable has a positive and significant effect on the relationship between information technology culture and online business success. However, Personal Innovativeness variable has a negative and significant effect relationship between information technology culture and online business success variable.